On the complicity of critique. An education-theoretical analysis of the contradictory involvement of critique - Herrmann, Katharina (Momentum Quarterly, 2016)
Critique intends to reveal and question existing power and governmental structures but cannot escape its own involvement in their stabilization and reproduction. Critical Bildung Theory considers this contradictory constitution of critique and determines it as a constitutive element of education. Based on argumentation figures of Critical Bildung Theory, the present contribution wants to investigate the complicity of supposedly subversive critique with integrative forces. In this context, the contradictory nature of critique relates not only to the object of criticism but also to the subjective conditions of contradicting. This raises the question of how an educational practice may look like which understands the functional moment of critique as the starting point for self-critical questioning about one’s own positioning and privileges.
Keywords: Contradictoriness of critique; Critical Bildung Theory; subject critique